Uterus didelphys associated with ovarian endometriosis in an infertile patient - Rudic Biljic-Erski, Ivana; Vasiljevic, Mladenko; Rakic, Snezana; Dzatic-Smiljkovic, Olivera; Mihajlovic, Sladjana (Vojnosanitetski pregled, 2021)
Abstract Introduction. Uterus didelphys results when Mullerian duct fusion is completely arrested during development. We presented a rare case of nonobstructive uterus didelphys occurring simultaneously with an endometriotic cyst of the ovary. Case report. A twenty-nine-year-old, nulliparous patient was admitted to our Clinic for laparoscopic treatment of an endometriotic ovarian cyst. Diagnoses of right ovarian endometriotic cyst and nonobstructed uterus didelphys were established with bimanual pelvic exam and two-dimensional transvaginal ultrasound. Diagnoses were subsequently confirmed by laparoscopy and magnetic resonance imaging. Laparoscopic incision and drainage of the endometriotic cyst were performed, followed by biopsy and coagulation of endometriotic lesions. Histopathology confirmed ovarian endometriosis. Gonadotropin-releasing hormone analogue (GnRHa) was prescribed postoperatively, for a total of 3 months. Ten months after completion of treatment, the patients was without disease recurence. Conclusion. Nonobstructive uterus didelphys is rarely associated with ovarian endometriosis.
Keywords: uterus; congenital abnormalities; ovary; infertility; endometriosis; laparoscopy; treatment outocme